2021
DOI: 10.21873/cdp.10064
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Utility of Geriatric Nutritional Risk Index After Curative Resection of Colorectal Cancer: A Propensity Score-matched Study

Abstract: Background/Aim: The geriatric nutrition risk index (GNRI) is a presumptive prognosticator in a variety of carcinomas. We investigated whether it similarly predicts outcomes of elderly patients with colorectal cancer (CRC). Patients and Methods: A total of 904 older adults (≥65 years) undergoing radical resections of CRC between April 2011 and December 2015 proved eligible for study. Each was grouped by preoperative status (cut-off point, 98) as low-level or normal GNRI, using propensity score matching to compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…25 of these were selected for further analysis. Finally, ten studies were deemed eligible for inclusion in the review (18)(19)(20)(23)(24)(25)(26)(27)(28)(29).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…25 of these were selected for further analysis. Finally, ten studies were deemed eligible for inclusion in the review (18)(19)(20)(23)(24)(25)(26)(27)(28)(29).…”
Section: Resultsmentioning
confidence: 99%
“…Only one study by Kataoka et al ( 25 ) did not report outcomes as adjusted ratios and hence could not be included in the meta-analysis. In their study, the authors used propensity score matching to compare data of patients with low and high GNRI (cut-off 98).…”
Section: Resultsmentioning
confidence: 99%
“…Although PNI was not evaluated in the geriatric colorectal cancer group when the literature was examined, PNI, which is an indicator of immune nutritional status, was found to be higher in the group under 65 years of age. In the geriatric population, the Geriatric Nutrition Risk Index (GNRI) calculated by using body weight and albumin instead of PNI was established, and survival and prognosis were found to be better in those with higher levels [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Body weight, height, and blood samples were obtained from each patient within 2 weeks before the start of neoadjuvant treatment (pre-treatment) and within 1 week before radical resection (post-treatment). Cut-off values (<98) for GNRI low and high groups were determined according to previous reports (13,(17)(18)(19)(20).…”
Section: Patientsmentioning
confidence: 99%
“…GNRI is calculated using serum albumin levels and the patient's height and body weight, making it objective and easy to use in clinical practice. Since its inception, various studies have shown the prognostic value of GNRI for patients with a range of gastrointestinal cancers (14)(15)(16), including colorectal cancer (17)(18)(19)(20)(21). A recent meta-analysis of 10 studies and a total of 3,802 colorectal cancer patients showed low GNRI to be signi cantly associated with poorer overall survival and disease-free survival (22).…”
Section: Introductionmentioning
confidence: 99%